ANALISIS KINERJA KEUANGAN SEBAGAI BAROMETER KINERJA PEMERINTAH DAERAH KABUPATEN MAROS SULAWESI SELATAN - Didi Permadi Sukur; Jamaluddin Majid; Suhartono Suhartono; Roby Aditiya (Universitas Islam Negeri Alauddin Makassar, 2021)
The results of the study show the following: 1) The financial performance of the local government of Maros Regency in terms of the effectiveness ratio is in the effective category for the 2017-2019 fiscal year, while the 2020 budget year is in the less effective category due to the covid-19 pandemic; 2) The financial performance of the Maros district government in terms of the efficiency ratio during the 2017-2020 fiscal year is in the less efficient category. This is a separate alarm for the local government of Maros Regency to be wiser in determining and managing its regional budget; 3) The financial performance of the local government of Maros Regency in terms of the activity ratio is in the poor category because during the 2017-2020 budget year the ratio of operating spending is higher than the ratio of investment spending. In the future, the investment spending ratio should be more dominant in order to maintain public trust and maintain the sustainability of the financial performance of the Maros Regency local government in the long term; 4) The financial performance of Maros Regency in terms of the PAD growth ratio is in the bad category. In addition to the ratio which has continued to decline since the 2017 fiscal year, the ratio has also never reached 25%. This of course must be addressed by the local government of Maros Regency because the PAD target continues to increase every year so that its realization must also continue to be boosted.